Male and Female Juvenile Delinquency: An Assessment of Contextual Differences in Offending - Cunningham, Mark A. (2002)
This thesis examines data on gender and the incidence and prevalence of delinquent and criminal offending, as well as gender differences in the context of offending for a sample of high school students in Omaha, Nebraska. Context refers to the specific attributes of a particular offense, whose interrelationship describes both the features and the circumstances of the offense. A focus on gender differences in the context of offending highlights how gender impacts the structural and social conditions that are related to commission of delinquent and criminal acts, and the findings of this study underscore the importance of this research. Results indicate that females offend in fewer settings and in different manners than their male counterparts. For example, females in the study primarily committed theft offenses in department stores at shopping malls, and were much more likely than males to commit such offenses with other individuals rather than alone. Furthermore, the results indicate that for less serious forms of delinquent behavior, such as skipping school and running away from home, the incidence and prevalence of such offenses are very similar for both genders. Such findings impact not only the development of delinquency theory, but also play an important role in the evaluation of gender differences in juvenile justice processing